2016
DOI: 10.1182/bloodadvances.2016000760
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of disease relapse in patients allografted for acute myeloid leukemia

Abstract: Key Points• We identify genes prognostic of disease relapse in patients allografted for AML.• Mutational profiles often change at relapse postallograft, which may have implications for the design of posttransplant interventions.Disease relapse is the major cause of treatment failure after allogeneic stem cell transplantation (allo-SCT) in acute myeloid leukemia (AML). To identify AML-associated genes prognostic of AML relapse post-allo-SCT, we resequenced 35 genes in 113 adults at diagnosis, 49 of whom relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 47 publications
(42 reference statements)
1
58
2
Order By: Relevance
“…Sequencing was performed on an Illumina MiSeq with 300 bp paired-end reads, yielding an average read depth of 912 reads per amplicon. Fluorescent capillary electrophoresis was performed in addition to NGS for the detection of FLT3 internal tandem duplications (ITD), because the rate of detection of ITDs is $60% using NGS alone (18). Details of NGS methodology is provided within Supplementary Information (Supplementary Tables S1-S3).…”
Section: Translational Relevancementioning
confidence: 99%
“…Sequencing was performed on an Illumina MiSeq with 300 bp paired-end reads, yielding an average read depth of 912 reads per amplicon. Fluorescent capillary electrophoresis was performed in addition to NGS for the detection of FLT3 internal tandem duplications (ITD), because the rate of detection of ITDs is $60% using NGS alone (18). Details of NGS methodology is provided within Supplementary Information (Supplementary Tables S1-S3).…”
Section: Translational Relevancementioning
confidence: 99%
“…Most mutations involve genes whose products have a tumor suppressive (e.g., PTEN) or a proliferative (e.g., KRAS) function. Thanks to this proliferative advantage leukemic cells may outnumber the anti-tumor activity of T cells, thereby promoting immune escape by these newly mutated clones [71,72].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…With the development of next-generation sequencing, investigators have reported that AML relapse occurring after chemotherapy often gains and loses subclones containing unique somatic variants, including putative driver mutations [87][88][89][90][91]. Recent studies investigating clonal evolution after HSCT relapses have focused on mutations in recurrently mutated AML genes, and while the presence of certain mutations can predict higher risk for relapse, the mechanisms by which these mutations may promote relapse remain unclear [92][93][94].…”
Section: T-cell Immune Reconstitution: Summarymentioning
confidence: 99%